Border-crossing and walling states in humanitarian work in Kolkata - Novikov, Egor (Walling, boundaries and liminality, 2019)
This chapter investigates how the transformative facilities of walling and sanctioned transgression are implemented in the Kalighat Home for the Dying Destitutes (NirmalHriday) in Indian Calcutta. Founded by Saint Teresa of Calcutta, or Mother Teresa, and currently run by her monastic order Missionaries of Charity the shelter welcomes dozens of both religious and non-religious volunteers every year. Separated from the intense urban life within the walls of the institution, the volunteers engage in direct interaction with the difference. This is a study of how the combination of physical and symbolic borders enables and navigates the transgressive experiences, how it transforms the volunteers’ identities.